Analisis Pengaruh Investasi, Inflasi, Kurs Dollar Amerika Serikat Dan Suku Bunga Kredit Terhadap Ekspor Indonesia Tahun 1992-2012 - Mahendra, I Gede Yoga; Kesumajaya, I Wayan Wita (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 5, Mei 2015 (pp. 348 - 607), 2015)
Export usually conduct by country who needs certain goods from another country. It gives lot of benefits and is an important income sources for developing countries such as Indonesia to support its development. Export can increase Indonesia’s income significantly. And thus, this research meant to know the simultaneous or partial effect of investment, inflation, US Dollar exchange rate and lending rate toward Indonesian export in 1992-2012. Another reason would be finding free variable that dominantly affected Indonesian export at that time. Therefore, the data analysis chose was multiple linear regression. From the research, writer found out that investment, inflasion, US Dollar exchange rate and lending rate had simultaneously influencing Indonesian export in 1992-2012. Meanwhile in partial way, US Dollar exchange rate and lending rate considerably influenced Indonesian export saved for the invenstment and inflasion. Henceforth, variable of US Dollar exchange rate showed dominant role toward Indonesian export in that years.
Keywords: export; investment; inflation; exchange rate; interest rate